Effects of self-acceptance on prosocial behavior: the mediating role of self-esteem - Li, Yuting; Guo, Li; Yang, Guane; Wu, Ying (Frontiers in Psychology, 2025)
ObjectiveProsocial behavior is significant for individual and social development. Although self-acceptance and self-esteem are considered important factors influencing prosocial behavior, how self-acceptance affects prosocial behavior and the role that self-esteem plays in it are unclear. Therefore, this study aimed to explore the relationships among self-acceptance, self-esteem and prosocial behavior and to verify the mediating role of self-esteem between self-acceptance and prosocial behavior.MethodsThis study was divided into three stages: first, interviews were used to construct the relationships among the three variables; second, a cross-sectional survey was conducted to establish a preliminary model; and finally, a six-month follow-up study was conducted with college students at a medical school in Shanxi, where cross-lagged analyses were used to test the direct effect of self-acceptance on prosocial behavior and the mediating role of self-esteem.Results(1) There was a significant positive correlation between self-acceptance, self-esteem and prosocial behavior; (2) self-esteem fully mediated the relationship between self-acceptance and prosocial behavior; and (3) This study validated the mediating model in which self-acceptance indirectly promotes prosocial behavior by enhancing self-esteem among medical university students, suggesting the importance of cultivating self-acceptance and self-esteem for promoting prosocial behavior in university students.